TBat: A Novel Strategy for Minimization of T-Way Interaction Test Suite Based on the Particle Swarm Optimization and the Bat Algorithm - Kamal Z., Zamli; Alsariera, Yazan A. (2016)
Our continuing dependencies on software raise issues of reliability. Lack of testing can lead to disastrous consequences including loss of data, loss of fortunes as well as loss of lives. For these reasons, many combinations of possible input parameters, hardware/software environments, and system conditions need to be checked against for conformance based on the system’s specification. Often, this results into combinatorial explosion of test cases. This project develops a novel strategy to minimize the test consideration using the Particle Swarm Optimization and the Bat Algorithm.